Role of the Peruvian American Medical Society (PAMS) in North-South medical cooperation. A historical perspective - Valdivieso Rodríguez, Manuel (2022)
This essay is a review of the main activities carried out by the Peruvian American Medical Society (PAMS) in terms of health cooperation in Peru. In the last 48 years, PAMS activities have been evolving, going from assistance through medical missions, to capacity transfer and strengthening of Medical Education in Peru. Likewise, PAMS has demonstrated the capacity to provide support in contingency situations, such as the latest activities in support of the country during the COVID-19 Pandemic. The lessons learned from this cooperative experience are analyzed, recognizing future possibilities that may contribute to the strengthening of the Peruvian Health System.